Polskie źródła „wielojęzyczności" Joyce ’a w Finnegans Wake - Szczerbowski, Tadeusz (Stylistyka, 2021)
One of the most neglected sources of Joyce’s ’multilingualism’ in Finnegans Wake is the Polish romantic movement. The article compares Polish elements in Finnegans Wake to a vocabulary in severa! poems (Mickiewicz’s Pan Tadeusz and Sonety krymskie, Juliusz Słowacki’s Król Duch). Joyce’s aposteriorism in Finnegans Wake results from his resistance to the arbitrary character of linguistic signs. Multilingualism creates a need to search for new contexts (Szczerbowski 2000).